Prevalence, risk factors, and prognostic implications of intraoperative bleeding during CF-LVAD implant - Ibrahim Mortada, MD; Christos Kourek, MD, PhD; Rupesh Kshetri, MD; Arun Singhal, MD; Anthony Panos, MD; Alexandros Briasoulis, MD, PhD; Mohammed Mhanna, MD, MPH; Shareef Mansour, MD; Kristine Yumul, MD; Paulino Alvarez, MD; Ernesto Ruiz Duque, MD (JHLT Open)
Background: The use of continuous flow left ventricular assist device (CF-LVAD) has revolutionized the management of advanced heart failure. One of the major complications associated with its use is the risk of bleeding, especially in the early postoperative period. Early events of postoperative bleeding have been associated with higher morbidity and mortality rates. Our study aims at identifying potential predictors of intraoperative bleeding, defined as 4 or more units of packed red blood cells transfused during surgery. A single-center retrospective cohort study of adult patients older than 18 years old who underwent CF-LVAD implantation between 2009 and 2024. Methods: Data were collected for the duration of implant hospitalization, including perioperative invasive hemodynamics, echocardiography, operative details, mechanical circulatory support, antiplatelets, inotropes, bleeding events, and blood product use, in addition to patient history and baseline characteristics. Results: A total of 208 patients were included in the analysis. Intraoperative bleeding occurred in 43 (20.67%) patients while 165 (79.33%) patients did not experience bleeding. Multilogistic regression analysis showed that artery bypass grafting pre-LVAD (odds ratio [OR] 2.98, confidence interval [CI] 1.2-7.42, p = 0.01) and temporary mechanical assist device pre-LVAD (OR 3.67, 95%CI 1.72-7.85, p < 0.001) were independent predictors of intraoperative bleeding during hospitalization. Intraoperative bleeding is also correlated with worse clinical outcomes, higher 90-day mortality (hazard ratio [HR] 10.4, p < 0.01, CI 95% 3.28-33.38) 206 subjects with 14 failures. Conclusion: History of coronary artery bypass grafting and mechanical circulatory support before the implantation of LVAD are independent predictors of intraoperative bleeding during hospitalization in these patients. Intraoperative bleeding is associated with higher frequency of right ventricle failure post-LVAD and higher 90-day mortality.